Intrinsic motivations and the non-profit health sector: evidence from Ethiopia - Danila Serra; Pieter Serneels; Abigail Barr (Institute for the Study of Labor (IZA), 2010)
Economists have traditionally assumed that individual behavior is motivated exclusively by extrinsic incentives. Social psychologists, in contrast, stress that intrinsic motivations are also important. In recent work, economic theorists have started to build psychological factors, like intrinsic motivations, into their models. Besley and Ghatak (2005) propose that individuals are differently motivated in that they have different missions, and their self-selection into sectors or organizations with matching missions enhances organizational efficiency. We test Besley and Ghatak's model using data from a unique cohort study. We generate two proxies for intrinsic motivations: a survey-based measure of the health professionals' philanthropic motivations and an experimental measure of their pro-social motivations. We find that both proxies predict health professionals' decision to work in the non-profit sector. We also find that philanthropic health workers employed in the non-profit sector earn lower wages than their colleagues.
Keywords: C93; I11; J24; 330; Sector choice; intrinsic motivation; non-profit; Gesundheitsberufe; Motivation; Nonprofit-Organisation; Gesundheitswesen; Äthiopien